2006
DOI: 10.1118/1.2198168
|View full text |Cite
|
Sign up to set email alerts
|

Absolute depth-dose-rate measurements for an Ir192 HDR brachytherapy source in water using MOSFET detectors

Abstract: This article was originally published as Zilio. VO, Joneja, OP, Popowski, Y et al, Absolute depth-dose-rate measurements for an 192Ir HDR brachytherapy source in water using MOSFET detectors, Medical Physics, 33(6) Reported MOSFET measurements concern mostly external radiotherapy and in vivo dosimetry. In this paper, we apply the technique for absolute dosimetry in the context of HDR brachytherapy using an 192 Ir source. Measured radial dose rate distributions in water for different planes perpendicular to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Once MOSkins were calibrated in a reference condition, a more complex arrangement representing a typical prostate implant was used to investigate the MOSkin detectors in a clinical setup. In fact, with an accurate and reproducible geometrical disposition of the needles, the study demonstrated that the MOSkins reproducibility was very high and that possible angular and energy dependences (Cygler et al, 2006;Zilio et al, 2006;Hardcastle et al, 2010;Qi et al, 2012) do not significantly affect dose measurements. The obtained results are very promising and of particular clinical importance.…”
Section: Moskin Calibration With the Ir-192 Brachytherapy Sourcementioning
confidence: 92%
See 1 more Smart Citation
“…Once MOSkins were calibrated in a reference condition, a more complex arrangement representing a typical prostate implant was used to investigate the MOSkin detectors in a clinical setup. In fact, with an accurate and reproducible geometrical disposition of the needles, the study demonstrated that the MOSkins reproducibility was very high and that possible angular and energy dependences (Cygler et al, 2006;Zilio et al, 2006;Hardcastle et al, 2010;Qi et al, 2012) do not significantly affect dose measurements. The obtained results are very promising and of particular clinical importance.…”
Section: Moskin Calibration With the Ir-192 Brachytherapy Sourcementioning
confidence: 92%
“…A number of different systems to perform in vivo dosimetry have been developed, including passive integrating thermoluminescent dosimeters (TLDs) and active methods based on diodes, diamond detectors, optical fiber-coupled scintillators and MOSFETs (Fagerstrom et al, 2008;Rustgi, 1998;Toye et al, 2009;Waldhäusl et al, 2005;Zilio et al, 2006). Some of these have already been used to perform in vivo prostate dosimetry by directly placing them in either a needle in the prostate, a catheter in the urethra or in the rectum (Seymour et al, 2011;Suchowerska et al, 2011 .…”
Section: Trus-probe Integratedmentioning
confidence: 99%
“…New detectors such as fiber optic coupled scintillation dosimeters , Therriault-Proulx et al 2011 and metal oxide semiconductor field effect transistors (MOSFETs) (Zilio et al 2006, Fagerstrom et al 2008 have recently been introduced to perform in vivo dosimetry. In particular, MOSFETs show many advantages, such as good spatial resolution, high sensitivity, real time read-out without deterioration of information, negligible radiation field perturbation owing to their small size and ease of use.…”
Section: In Vivo Dosimetry In Radiotherapymentioning
confidence: 99%
“…All microMOSFETs were calibrated in Ir-192 source with known calculated dose before their clinical use is sensitive to the distance, calibrations need special attention [9]. Zilio et al [12] measured the absolute depth dose rates of (Figure 2). The microMOSFET flex was fixed inside the last catheter at a distance of 4.5 cm from its tip, taking care that the measurement point still lies inside the CTV.…”
Section: Calibration Of Micromosfet With Flexible Tube Cathetersmentioning
confidence: 99%